2022
DOI: 10.1371/journal.pone.0262549
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated fibroblasts increase interleukin-6 expression and induce migration of head and neck squamous cell carcinoma

Abstract: Background Cytotoxic effects of radiation play an important role in the treatment of head and neck cancer. However, irradiation is known to lead to the migration of various cancer cells, including those of head and neck cancer. Recently, fibroblasts in the cancer microenvironment have been reported to be involved in this mechanism. Nevertheless, the mechanism underlying migration of head and neck cancer cells remains unclear. Herein, we aimed to elucidate this migration mechanism induced by irradiation in term… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
(44 reference statements)
0
3
2
Order By: Relevance
“…Surprisingly, despite 15 out of the 36 cytokines investigated being detectable in the chip effluent, no significant changes in cytokine release were observed following irradiation with 5 × 2 Gy. This contrasts with studies on HNSCC cell lines, which found that irradiation (2, 5 and 10 Gy) stimulated the release of IL6 within 24 h post-irradiation from fibroblasts, which will be present in the tumour biopsy samples, as well as reducing the survival of HNSCC cells [62]. Suzuki et al [62] also found that the migration of HNSCC cells induced by irradiated fibroblasts was mediated by IL6, although this may simply represent the differences between the 2D cell line culture and the 3D tissue where the number of fibroblasts will be lower.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Surprisingly, despite 15 out of the 36 cytokines investigated being detectable in the chip effluent, no significant changes in cytokine release were observed following irradiation with 5 × 2 Gy. This contrasts with studies on HNSCC cell lines, which found that irradiation (2, 5 and 10 Gy) stimulated the release of IL6 within 24 h post-irradiation from fibroblasts, which will be present in the tumour biopsy samples, as well as reducing the survival of HNSCC cells [62]. Suzuki et al [62] also found that the migration of HNSCC cells induced by irradiated fibroblasts was mediated by IL6, although this may simply represent the differences between the 2D cell line culture and the 3D tissue where the number of fibroblasts will be lower.…”
Section: Discussioncontrasting
confidence: 76%
“…This contrasts with studies on HNSCC cell lines, which found that irradiation (2, 5 and 10 Gy) stimulated the release of IL6 within 24 h post-irradiation from fibroblasts, which will be present in the tumour biopsy samples, as well as reducing the survival of HNSCC cells [62]. Suzuki et al [62] also found that the migration of HNSCC cells induced by irradiated fibroblasts was mediated by IL6, although this may simply represent the differences between the 2D cell line culture and the 3D tissue where the number of fibroblasts will be lower. The secretion of cytokines into the effluent over the incubation time on the perfusion device further supports the maintenance of the functionality of the tissue ex vivo.…”
Section: Discussioncontrasting
confidence: 76%
“…It might be possible that due to the time distance from the injury, parts of the produced IL-6 had already been degraded. According to other studies, irradiation can increase or decrease IL-6 expression; so, in general, it seems that irradiation influences the gene expression of IL-6 just slightly [47,48].…”
Section: Discussionmentioning
confidence: 87%
“…Suzuki et al showed faster migration of HNSCC cells (SAS and FaDu cell lines) in co-cultures with fibroblasts, especially after their irradiation. They also confirmed that the migration of HNSCC cells was induced by fibroblast-secreted IL-6 [ 22 ]. However, unlike our methodology, the Suzuki group performed a migration assay with a mechanical barrier between HNSCCs and fibroblasts.…”
Section: Discussionmentioning
confidence: 67%